(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study examines the levels of stress and the effectiveness of stress management practices among employees in private and public sector banks. Using a mixed-methods approach, the research investigates the sources of stress, coping mechanisms, and organizational support available to employees. Quantitative data were collected through surveys, while qualitative insights were gathered from in-depth interviews, providing a comprehensive understanding of the stress landscape in both sectors. Findings reveal significant differences in stress levels and management strategies between the two sectors, with public sector employees experiencing more stress from bureaucratic procedures and job monotony, while private sector employees face intense performance pressure and job insecurity. The study highlights the critical role of tailored stress management practices, emphasizing the need for streamlined processes and job variation in public banks, and realistic performance targets and better work-life balance in private banks. These insights offer valuable guidance for both sectors to enhance employee well-being and productivity. The research underscores the importance of continuous professional development and effective leadership in mitigating stress and promoting a healthier work environment.